Embodied practice: rediscovering the 'heart' of nursing. (27th March 2014) - Draper, Jan
Abstract Aim This article explores the importance of embodiment in nursing. It examines different sources of authoritative knowledge concerning the body and embodiment. It argues that dominant scientific and medical epistemologies of the body have displaced and marginalized embodied epistemologies, creating only a partial understanding of the embodied experiences of our patients and our own embodiment as nurses. Background Over the last 20 years, there has been a rapid expansion of theoretical literature concerning the body and embodiment, spanning a range of disciplines. The potential of these insights to the essentially 'body‐based' practice of nursing is highly significant. However, although work in this area is now increasing, theoretical and empirical investigation of the body and embodiment in nursing has remained relatively neglected. Design Discussion paper. Data Sources Conventional approaches to systematic searching of the literature were not adopted for this conceptual paper. Seminal texts predominantly from nursing and sociology accompanied by more recent sources were used as a platform for theoretical reflection and to inform development of the conceptual arguments. Implications for Nursing The paper proposes a corporeal (re)turn to nursing practice, one that recognizes the lived embodied experience of the patient and the embodied skill and knowledge of the nurse and examines the implications for contemporary person‐centred nursing practice, research and education. Conclusion At a significant juncture in nursing's history, when there is greater international focus on delivering higher standards of care, the paper calls for a repositioning of the place of embodiment in nursing.